A Data Processing Algorithm in EPC Internet of Things - Huiqun Zhao; Chuancong Huang (2014 International Conference on Cyber-Enabled Distributed Computing and Knowledge Discovery, 2014)
With the rapid growth of data which sensed by the sensor nodes deployed in the logistics center, the current data processing methods have been impossible to meet the requirements of rapid and efficient analysis and processing for big data. In order to satisfy the demand, this paper designs a data processing algorithm which is implemented by Hadoop. The experimental results show that our method can greatly improve the system efficiency of data processing.